2007
DOI: 10.1109/wacv.2007.15
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Extraction of Femur Contours from Calibrated Fluoroscopic Images

Abstract: Automatic identification and extraction of bone contours from x-ray images is an essential first step task for further medical image analysis. In this paper we propose a 3D statistical model based framework for the proximal femur contour extraction from calibrated x-ray images. The automatic initialization is solved by an Estimation of Bayesian Network Algorithm to fit a multiple component geometrical model to the x-ray data. The contour extraction is accomplished by a non-rigid 2D/3D registration between a 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Experimental methods for patient-specific QA in advanced radiotherapy are, however, time-consuming in both manpower and accelerator time and have been shown to be unable to detect some unacceptable plans. [6][7][8][9][10][11] Recent studies have demonstrated a sensitivity of only 5% to detect IMRT plan errors using IMRT pretreatment measurements. 12,13 Moreover, as treatment planning becomes more efficient and the number of patients treated with advanced radiotherapy techniques steadily increases, measurement-based verification may result in a continued increase in workload.…”
Section: Review Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental methods for patient-specific QA in advanced radiotherapy are, however, time-consuming in both manpower and accelerator time and have been shown to be unable to detect some unacceptable plans. [6][7][8][9][10][11] Recent studies have demonstrated a sensitivity of only 5% to detect IMRT plan errors using IMRT pretreatment measurements. 12,13 Moreover, as treatment planning becomes more efficient and the number of patients treated with advanced radiotherapy techniques steadily increases, measurement-based verification may result in a continued increase in workload.…”
Section: Review Of the Problemmentioning
confidence: 99%
“… 1 In spine surgery, the registration of single vertebrae is mostly used for pedicle screw placement and cement reinforcement. 2 , 3 , 4 For total hip replacement, the registration is used for intra‐operative positioning of the femoral implant 5 , 6 , 7 and post‐operative analysis of cup placement. 8 , 9 , 10 In orthopedic diagnostics, the 3D curvature of scoliotic spine 11 and the scoliotic rib cage were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exploration of extracting landform features from CL data is also necessary for hydrological applications. Based on a Delaunay triangulation built from CLs, skeleton construction techniques have been proposed to extract the landform features by using "flat triangles" [41] or "crust and skeleton extraction" [9]. However, the skeleton construction methods usually fail to create topologically correct drainage systems, due to the lack of connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The image-to-model correspondence is established using a non-rigid 2D point matching process, which iteratively uses a symmetric injective nearestneighbor mapping operator and 2D thin-plate splines based deformation to find a fraction of best matched 2D point pairs between features detected from the fluoroscopic images and those extracted from the 3D model. The image contours of the proximal femur are extracted from the input images by a graphical model based Bayesian inference [6] whereas the apparent contours of the 3D model are extracted using an approach described in [7]. The obtained 2D point pairs are then used to set up a set of 3D point pairs such that we turn a 2D-3D reconstruction problem to a 3D-3D one.…”
Section: D/3d Reconstruction Schemementioning
confidence: 99%
“…The 3D/3D reconstruction problem is then solved optimally in three sequential stages. For details, we refer to our previous works [4] and [6].…”
Section: D/3d Reconstruction Schemementioning
confidence: 99%